Preparation and Determination of Rheological Behavioour of Fine Strontium Titanate Powder Suspensions - Ünal, Uğur; Çiftçioğlu, Muhsin (Izmir Institute of Technology, 1999)
In this project, strontium titanate powders were prepared by using solgel and Pechini methods. In sol-gel method, the powders were prepared by mixing the Ti02 sol and Sr(N03h solution. Precipitation was observed after the addition of Sr(N03)2 solution. Two powders were prepared by each method. In sol-gel method, acid:alcohol ratio was changed. In Pechini method, 50% of citric acid was substituted with polyacrylic acid. The characterization of the powders were performed by Fourier Transform Infrared Spectrophotometer (FTIR), Thermogravimetric Analyzer (TGA), Scanning Electron Microscope (SEM), X-Ray Diffraction and Optical Microscope. The calcination temperature of 650°C was chosen for sol-gel powder according to TGA data. XRD pattern showed that this temperature was not high enough to form complete SrTi03 phase, but no peaks related to nitrates or organic groups was observed in FTIR spectra. Sintering studies indicated that the agglomeration of sol-gel powder was very strong because the relative densities were very small. Pechini powders had weaker agglomerates and sintered to higher densities. The diameters of the Pechini powders were found as in the range of 0.2-0.5 um. The powders were dispersed in white oil and the rheological behaviour of these dispersions was studied by a rheometer. Several runs at different shear rates, and volume fractions were done. The suspensions without surfactant showed shear-thinning behavior, which indicates that the suspensions were flocculated. The addition of surfactant in certain amount produced stabilized suspenSIOns. The stabilized suspenSIOns showed Newtonian or Dilatant behaviour. The increase in the solids loading did not show significant change in the viscosity of stabilized suspension.
Thesis (Master)--Izmir Institute of Technology, Materials Science and Engineering, Izmir, 1999
Includes bibliographical references (leaves: 70-74)
Text in English; Abstract: Turkish and English
x, 74 89 leaves
Keywords: TA418.14 .U53 1999; Rheology; Strontiun--Analysis; Analysis